RESULTS OF THE FIRST YEAR OF THE PROJECT ``CAD'' - Milan, KLEMENT (Trends in education, 2014)
The article presents the results and outcomes of the activities undertaken during the first year of the project CAD, or computer-aided technical drawing in schools, which is funded by the European Social Fund and by the Czech state budget. This joint project of the Department of Technical and Information Education PdF UP in Olomouc and partner schools (grammar schools) is focused on supporting the activities of the team, focused on methodological innovation in teaching implemented in secondary schools, and aimed at improving the teaching of practical applications of mathematics and chemistry, using computer aided technical drawing.
Keywords: AutoCAD; project activities; methodical preparation; training module.